CORPORATE GOVERNANCE REFORMS: CONTEMPORARY ISSUES OF ENVIRONMENTAL ACCOUNTABILITY - Bharti, Piyush; Prachi Kumari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India has had a succession of business scandals and environmental difficulties throughout the years, leading to a reassessment of corporate governance standards. In light of this, many regulatory agencies and committees have been formed to augment corporate governance practices within the nation. The Naresh Chandra Committee, Kumar Mangalam Birla Committee, Narayana Murthy Committee, and Uday Kotak Committee are prominent instances that underscore the significance of openness, independent monitoring, and ethical behaviour inside corporate entities. This paper aims to provide an overview of the topic, discussing its various aspects and the significance of corporate governance reform in India, which has become increasingly prominent due to its crucial role in promoting environmental accountability within the economic sector. It will cover a comprehensive summary of the convergence between corporate governance reform and environmental accountability within the specific context of India. Moreover, the issue of environmental accountability has become a significant matter of concern in India, owing to the escalating environmental problems it faces, such as pollution, depletion of resources, and climate change. In response to these concerns, there has been an increasing recognition of the significance of sustainability governance, which establishes a connection between corporate governance and the responsible management of the environment. This paper emphasises the necessity for Indian corporations to incorporate environmental factors into their corporate governance systems. It will examine the dynamic regulatory environment incentivising companies to disclose ecological risks, ESG Reports, implement sustainable strategies, climate change litigation, and participate in corporate social responsibility (CSR). Furthermore, it highlights the significance of stakeholders, such as investors and consumers, in influencing firms to enhance their environmental responsibility. India’s corporate governance reform process is developing to incorporate environmental accountability as a fundamental element. Integrating governance frameworks and ecological responsibility is vital for enterprises to address the complexities of the current era effectively and actively contribute towards India’s sustainable development objectives.